(untitled) (Fiep Bulletin - online, 2011)
The aim of this paper is to describe the organizing principles of quality care conducted in hospital management that focuses on the practice of quality management in a teaching hospital of the Federal University of Rio Grande do Norte, in accordance with the National Hospital Humanization. The program in focus aims to classify the care and labor relations, provide administrative rationality, encourage teamwork and be an important scenario for humanizing practices. We used a case study design and the analysis was performed on documents and experiential observations coming from the professionals who develop activities. The framework that guided the interpretation consisted of the principles of humanization contained in the National Hospital Humanization and comprehensive care. As a result, the study provides an understanding of humanizing practices that positively influence the quality management through extension projects involving employees, students and teachers of the institution. It is concluded that modernization in health management involves various levels of teaching and that service is an important tool in promoting quality care. It is believed that this form of management indicates the involvement of the hospital, as a teaching institution, in the promotion of humanization care and in the empowerment of users for the improvement of health services.